Kepribadian Humanis Pustakawan untuk Layanan Perpustakaan Berkualitas - Mufti Zevira (Nazharat: Jurnal Kebudayaan, 2024)
This article discusses the importance of a librarian's humanistic personality in an effort to improve the quality of library services. The humanistic personality of librarians involves not only technical skills in managing information, but also the ability to interact with library users empathetically and attentively. Librarians with humanistic personalities are able to create an environment that is welcoming, inclusive, and supportive of the intellectual and social development of library patrons. This research identifies key characteristics of a humanist personality, such as being patient, communicative, and attentive to individual needs, which form the basis for more responsive and quality library services. In addition, this article also analyzes how the development of humanist personality in librarians can contribute to the achievement of the library's goal as a center of learning and community empowerment. It is hoped that the results of this discussion can provide insights for relevant parties in designing librarian training programs that not only focus on technical skills, but also on developing attitudes and characters that support the best service for the community.